Hiraya Manawari. Volume 17 : Mga kwento ni Lola Basyang. (ABS-CBN.)
When Adelino, a small-town tailor with big dreams, tries on the chaleco of Senorito Rosaldo, one of his clients, he is suddenly seized with the desire to become a " senorito" He poses as Manuel Alfredo, the Seniorito's son.